2010
DOI: 10.4067/s0718-27242010000300004
|View full text |Cite
|
Sign up to set email alerts
|

The Spin-off Chain

Abstract: Several theories have been developed over a large number of years on the effort of localisation and exploitation of research results that take place in research laboratories and which can lead to the production of innovative products. This process is being facilitated by spin-off companies. The purpose of this paper is to shed light on this process of developing a spin-off company. To this goal a framework has been developed, namely “the Spin-off Chain”, which will be used as a guide and will provide to future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Klepper and Sleeper (2005) support the basic premise of the model that spinoffs inherit knowledge from their parents that shapes their nature at birth. Elpida, et.al (2010) found that spinoff ventures are seen as a vehicle for transferring knowledge into application in society. Entrepreneurship or more specifically the entrepreneurial action is seen as the core process in the development of spinoff ventures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Klepper and Sleeper (2005) support the basic premise of the model that spinoffs inherit knowledge from their parents that shapes their nature at birth. Elpida, et.al (2010) found that spinoff ventures are seen as a vehicle for transferring knowledge into application in society. Entrepreneurship or more specifically the entrepreneurial action is seen as the core process in the development of spinoff ventures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ultimately stating that within the university spin-off literature, special emphasis has been on the institutional context within a university and how this setting influences the business development process. Elpida et al (2010) reconcile spin-out creation models as explained above (such as the entrepreneurial process model and the four-stage model of Ndonzuau, Pirnay and Surlemont, (2002). A further model is reviewed such as the Universidad Politecnica de Valencia (UPV) spin-out creation model.…”
Section: Figure 1: the Entrepreneurial Process Of Spin-out Company Crmentioning
confidence: 99%
“…These seeds are accumulated to a pre-incubator phase to concrete concepts, configuring the Cells of Opportunities (Coo)." From the models discussed above, Elpida et al (2010) introduce their own model which integrates the above aspects of the entrepreneurial view and stages involved.…”
Section: Figure 1: the Entrepreneurial Process Of Spin-out Company Crmentioning
confidence: 99%
See 1 more Smart Citation
“…Esses autores não precisaram ir à Lua para perceber esse novo espírito, mas ficaram em seu próprio território, a França, para descreverem as transformações pelas quais a perspectiva de mundo estava passando. E a mudança que descrevem pode ser resumida como uma lógica de funcionamento empresarial, da qual podemos destacar aspectos como funcionamento em rede, autonomia, liberdade, flexibilidade, transferência de tecnologia, inovações tecnológicas, Quando ligado à transferência de tecnologia, spin-off pode ser traduzido como "derivagem", e é reconhecido como uma das formas de empreendedorismo que mais favorecem o crescimento econômico(ELPIDA et al, 2010). Trata-se daquilo que produzido pela indústria espacial, sobremaneira instalada nos países desenvolvidos, passa a ser transformado em geração de valor econômico em solo terrestre por meio de jogos de cooperação.…”
unclassified